Burdens from Men and the Wisdom of Women: Marriage and Feminism in Their Eyes Were Watching God - Pritchard, Katie (URJ-UCCS: Undergraduate Research Journal at UCCS, 2019)
Janie Crawford, the strong and independent female heroine of Zora Neale Hurston's novel, Their Eyes Were Watching God, marries three different men. This essay focuses on Janie's marriages to Joe Starks and Tea Cake and the enduring question from feminists critics of whether or not Janie finds her voice. Through Janie’s story and her marriages, Hurston offers an essential insight into the experience and wisdom of African-American women and their relationships with their community, the world, and themselves.